Independence Habituation of Autism Students in the Learning Management - Nanik Wilujeng; Tin Agustina Karnawati; Moh Bukhori (Universitas Negeri Malang, 2020)
This research aims to examine the independence habituation for students with autism in learning management at SMK (vocational high school) Tunas Bangsa, Malang. It covers the planning, implementation, and evaluation of the independence habituation in the learning process for students with autism. Besides, it studies the problems and solutions made during the application of the learning program. It is qualitative research with autistic students of grade XII as the subject. The informants of this research involved the headmaster; normative, adaptive, and productive teachers; the advisor of exceptional teachers; parents; and psychologists. The data collection methods include observation, interview, and documentation. The results of the study cover the planning, outcome, and learning implementation through the independence habituation of students with autism at SMK Tunas Bangsa, Malang. The learning independence appears from the development of the students’ independence. The problems found during the independence habituation process on the learning process are solved through some solutions applied by all of the educational elements of the comprehensive learning management at SMK Tunas Bangsa, Malang.